Pyrrhonian Skepticism in Diogenes Laertius - Vogt, Katja Maria (SAPERE, 2015)
This volume offers the first bilingual edition of a major text in the history of epistemology, Diogenes Laertius's report on Pyrrho and Timon in his Lives of Eminent Philosophers. Leading experts contribute a philosophical introduction, translation, commentary, and scholarly essays on the nature of Diogenes's report as well as core questions in recent research on skepticism.